The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1038/emm.2013.91
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin-induced Bcl-2 translocation and its phosphorylation in the nucleus trigger apoptosis in breast cancer cells

Abstract: Here, we report that B-cell lymphoma 2 (Bcl-2) is a novel target molecule of aspirin in breast cancer cells. Aspirin influenced the formation of a complex by Bcl-2 and FKBP38 and induced the nuclear translocation of Bcl-2 and its phosphorylation. These events inhibited cancer cell proliferation and subsequently enhanced MCF-7 breast cancer cell apoptosis. Bcl-2 knockdown using small interfering RNA (siRNA) delayed apoptotic cell death, which correlated with increased proliferation following aspirin exposure. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 45 publications
(53 reference statements)
3
29
1
Order By: Relevance
“…Therefore, we observed the changes in levels of Bcl2, BAX, and cleaved caspase-3 in rat TSCs and determined that aspirin-induced apoptosis occurs through the mitochondrial/ caspase-3 pathway. Our results from this study are similar to those found in previous research [32][33][34][35]. We confirmed our results using an immunofluorescence assay in rat Achilles tendons.…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, we observed the changes in levels of Bcl2, BAX, and cleaved caspase-3 in rat TSCs and determined that aspirin-induced apoptosis occurs through the mitochondrial/ caspase-3 pathway. Our results from this study are similar to those found in previous research [32][33][34][35]. We confirmed our results using an immunofluorescence assay in rat Achilles tendons.…”
Section: Discussionsupporting
confidence: 83%
“…However, this is not the case as ASA was unable to regulate COX-2 expression at protein level in MDA-MB-231 cells (Supplementary Figure S4). Thus, consistent with previous work, [33][34][35] it appears that the BC cell death by ASA is mediated by apoptosis through the regulation of Bax/ Bcl2 and Caspase-3 system. Although the role of COX-2 signaling in this event is unclear, the involvement of this signaling pathway cannot be ruled out.…”
Section: Dose-dependent Inhibitory Effect Of Asa On Bc Cell Viabilitysupporting
confidence: 79%
“…51,52 The results of in vitro as well as animal studies also found an association between ASA use and growth inhibition of BC cells. 33,53,54 Ironically, the results from clinical and preclinical studies are inconsistent, 52,55 and thus a dilemma emerged about the role of ASA in prevention or delaying BC growth. Given the importance of this dilemma, we investigated the impact of ASA on different BC cell growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, PIK3CA is one of the most commonly mutated genes in estrogen receptor positive (ER+) human breast cancer with mutation frequencies of 45% in the luminal A subtype and 29% in the liminal B subtype [10]. Epidemiological [11] and experimental studies [12] both supported a role for aspirin in the treatment of ER+ breast cancer.…”
Section: Introductionmentioning
confidence: 99%